2017
DOI: 10.1007/s10040-017-1571-7
|View full text |Cite
|
Sign up to set email alerts
|

The key role of supply chain actors in groundwater irrigation development in North Africa

Abstract: The role played by supply chain actors in the rapid development of groundwater-based irrigated agriculture is analyzed. Agricultural groundwater use has increased tremendously in the past 50 years, leading to the decline of water tables. Groundwater use has enabled intensification of existing farming systems and ensured economic growth. This “groundwater economy” has been growing rapidly due to the initiative of farmers and the involvement of a wide range of supply chain actors, including suppliers of equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Our study found that temperature and precipitation were the main climatic variables affecting CPP, which agreed well with previous studies [28][29][30][31]. Precipitation plays a stronger limiting role, suggesting that water resources are a major constraint to agricultural development, which is consistent with other studies [32][33][34][35][36][37]. The main contributing factor may be that North Africa has a particularly arid climate due to its location near the Tropic of Cancer, which is controlled and influenced by the subtropical high-pressure zone and the predominantly downward flow of air, making it a typical tropical desert climate and a Mediterranean climate.…”
Section: Spatial Analysis Of Constraints On Cppsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that temperature and precipitation were the main climatic variables affecting CPP, which agreed well with previous studies [28][29][30][31]. Precipitation plays a stronger limiting role, suggesting that water resources are a major constraint to agricultural development, which is consistent with other studies [32][33][34][35][36][37]. The main contributing factor may be that North Africa has a particularly arid climate due to its location near the Tropic of Cancer, which is controlled and influenced by the subtropical high-pressure zone and the predominantly downward flow of air, making it a typical tropical desert climate and a Mediterranean climate.…”
Section: Spatial Analysis Of Constraints On Cppsupporting
confidence: 93%
“…Due to the dry and hot climate, there is little precipitation throughout the year, making it difficult to form rivers and lakes, and therefore, water sources are strained. Because of this, the problem of water sources has become a bottleneck for the economic development of the North African region, especially for agricultural production [32][33][34][35][36][37].…”
Section: Spatial Analysis Of Constraints On Cppmentioning
confidence: 99%
“…Groundwater started to gain prominence through the action and investments of individual agents, leading Molle et al (2003, p. 2) to qualify it as a "silent revolution;" it was only recognized as an important resource by states much later. Access to land and water often involves informal arrangements framed within locally-agreed rules, arrangements and regulations (Shah, 2009;López-Gunn, Rica and van Cauwenbergh, 2012;Kuper et al, 2016;Lejars, Daoudi and Amichi, 2017). Informal networks around groundwater extraction extend well beyond the frontiers of the aquifer and actors operate in a context where access by farmers, not only to production factors (land, water, inputs) but also to markets, can be highly informal.…”
Section: The Groundwater Boom: the Silent Revolution Led By Private I...mentioning
confidence: 99%
“…In Morocco, climate change will negatively impact economic growth, particularly in rural areas, due to its adverse impacts on water availability, affecting agricultural production and yields (Van Praag, 2021; World Bank, 2022). The projected duplication of the frequency and duration of meteorological drought overall in the Northern Africa region (IPCC, 2022) together with the rapid change in the irrigation practices in Morocco (Lejars et al., 2017), among other factors, lead to unsustainable use of water resources.…”
Section: Introductionmentioning
confidence: 99%